Engineering Properties of Self-Compacting Concrete Produced by Polypropylene and Steel Fiber - Karatas, Mehmet; Gunes, Abdulkadir (Budapest Univ Technology Economics, 2015)
Fresh and hardened properties of self-compacting concrete (SCC), produced by polypropylene and steel fiber, were analysed in this study. Within the scope of the study, natural river aggregate with grain diameter of 15 mm and a modified polycarboxylate based super plasticizer were used 10% displaceable with silica fume CEM I 42.5N type cement, on the purpose of supporting the dust content of self-compacting concrete. Polypropylene and steel fiber in different rates were used both separately and together in self-compacting concrete samples and these were compared with fresh and hardened properties of non-fibrous self-compacting concrete. It was deduced from these test results that the fiber use in proper rates would contribute to the engineering properties of self-compacting concrete.
Keywords: Self-compacting concrete; fiber concrete; compressive strength; tensile strength in bending